Anatomy and Surgical Relevance of Rouviere’s Sulcus - Raja Dahmane; Abdelwaheb Morjane; Andrej Starc (The Scientific World Journal)
Rouviere’s sulcus (RS) (i.e., incisura hepatis dextra, Gans incisura) represents an important anatomical landmark. The aim of the study was to determine the frequency of the RS, its description, its location, its relations to the right portal pedicle and to the plane of the common bile duct, and the evaluation of the surgical relevance of the obtained data. Forty macroscopically healthy and undamaged livers were removed during autopsies from cadavers of both sexes. The RS was present in 82% of the cases and in these the open RS was identified in 70% of the livers. The fused type was observed in 12% of the cases; 18% of the livers had no sulcus. The mean length of the open type RS was 28 ± 2 mm (range 24–32 mm) and its mean depth was 6 ± 2 mm (range 4–8 mm). The right posterior sectional pedicle was found in the RS in 70% of the cases. In 5% of the livers, we also dissected a branch of the anterior sectional pedicle. Inside 25% of the RS, we found the vein of segment 6. The RS identification may avoid bile duct injury during laparoscopic cholecystectomy and enables elective vascular control during the right liver resection.